Super-heterodyne interferometer for non-contact dielectric measurements on millimeter wave material - Hock G.C.; Chakrabarty C.K.; Badjian M.H.; Devkumar S.; Emilliano (2023)
This paper describes the use of AD8302 evaluation board from Analog Devices in superheterodyne millimeter wave interferometer for dielectric measurement. The measurements are performed without direct contact on the millimeter wave material. Signals from the output of two mixers in the interferometer were obtained for phase shifting analysis. They are used as inputs to the evaluation board. The output from the evaluation board was connected to computer for data processing. The voltage values obtained from the board was then converted to phase angle by using the pre-calibrated data and LabView graphical programming language. 2008 IEEE.